Effects of an art-based intervention in older adults with mild cognitive impairment: a randomised controlled trial. (23rd July 2022) - Lin, Rong; Luo, Yu-ting; Yan, Yuan-jiao; Huang, Chen-shan; Chen, Li-li; Chen, Ming-feng; Lin, Mo-jun; Li, Hong
Abstract: Background: Art-based interventions may delay cognitive decline and improve health-related outcomes in older adults with mild cognitive impairment (MCI). Objective: To examine the effects of the Creative Expressive Arts-based Storytelling (CrEAS) program compared to active and waitlist controls on neurocognitive and other health-related outcomes in older people with MCI. Design: Three-arm parallel-group, randomised controlled design. Participants: One-hundred and thirty-five adults with MCI (mean age: 70.93 ± 6.91 years). Methods: Participants were randomly assigned to intervention (CrEAS, n  = 45), active control ( n  = 45) or waitlist control ( n  = 45) groups. Interventions were applied once per week for 24 weeks. The primary outcome was global cognitive function; secondary outcomes were specific cognition domains (memory, executive function, language and attention) and other health-related outcomes (anxiety, depression and quality of life [QoL]). All variables were measured at baseline (T0), 24-week follow-up (T1) and 48-week follow-up (T2). Results: Participants in the CrEAS group showed significantly higher global cognitive function (adjusted mean difference [MD] = −0.905, 95% confidence interval [CI] −1.748 to −0.062; P  = 0.038) and QoL (adjusted MD = −4.150, 95% CI -6.447 to −1.853; P  = 0.001) and lower depression symptoms (adjusted MD = 2.902, 95% CI 0.699–5.104; P  = 0.011) post-intervention at the 24-week follow-up compared with the active control group. At 48-week follow-up, only the Auditory Verbal Learning Test Immediate recall score was significantly improved compared with the active control group (adjusted MD = −2.941, 95% CI −5.262 to −0.620; P  = 0.014). Conclusions: Older adults with MCI who participated in the CrEAS program improved their neuropsychological outcomes and QoL and reduced their rate of cognitive deterioration.